Resilient Modulus Assessment of Asphalt Mixture Incorporating Fly Ash Geopolymer - Bahri, Aimie Nurshuhada; Aman, Mohamad Yusri (Recent Trends in Civil Engineering and Built Environment, 2021)
An increasing a traffic volume, higher axle loads and increased tire pressure influencing the pavement damage and accumulation of permanent deformation caused by repeated loads at high working temperatures. Due to these phenomena, road construction industry needs to focus how to improve the characteristics of asphalt mix by incorporating with fly ash geopolymer. This study aims to evaluate the effects of fly ash geopolymer with 0%, 3%, 5%,7%,9% and 11% by mass of total mixture. Conventional binder 80/100 penetration grade was used as the base binder. The asphalt mixture prepared with varies percentage of fly ash geopolymer was evaluated for resilient modulus using universal testing machine. The optimum binder content conducted using Superpave method indicates the percentage of bitumen content increase as the fly ash geopolymer increases. It can be concluded that the asphalt mixture incorporation of 9% fly ash geopolymer give the highest resilient modulus values and lowest horizontal deformation compared to the other specimens. Based on these results, mixes incorporating fly ash geopolymer has the potential to improve the deformation regardless of test temperature.